Xylooligosaccharides induce stomatal closure via salicylic acid signaling‐regulated reactive oxygen species and nitric oxide production in Arabidopsis. Issue 4 (11th April 2021) - Zhang, Cheng; Song, Zhiqiang; Jin, Pinyuan; Zhou, Xiuhong; Zhang, Huajian
Abstract: Xylooligosaccharides (XOS) are the major coproducts of biofuel production and the most representative functional sugar enhancing animal physiology. However, little is known regarding the biological relevance of XOS to plants. Here, we found XOS triggered stomatal closure in Arabidopsis in a dose‐dependent manner. Pamarcological data showed that XOS‐induced stomatal closure was markedly inhibited by catalase (CAT, a reactive oxygen species [ROS] scavenger), salicylhydroxamic acid (SHAM, a peroxidase inhibitor), and 2‐(4‐carboxyphenyl)‐4, 4, 5, 5‐tetramethylimidazoline‐1‐oxyl‐3‐oxide (cPTIO, a nitric oxide [NO] scavenger). Moreover, XOS induced the production of ROS and NO in guard cells of Arabidopsis . ROS production was strongly restricted by CAT and SHAM, but was unaffected by treatment with diphenyleneiodonium chloride (DPI, an NADPH oxidase inhibitor) or cPTIO. NO production was suppressed by CAT, SHAM, and cPTIO, but not by DPI. The elevation of ROS level mediated by SHAM‐sensitive peroxidases occurred upstream of NO. Additionally, XOS‐triggered stomatal closure and ROS and NO accumulation were significantly impaired in npr1 (salicylic acid signaling) mutant plants, but were not in jar1 (jasmonic acid signaling) or ein2 (ethylene signaling) mutant plants. Furthermore, XOS‐induced stomatal closure was unaffected in both ost1 and atrbohD atrbohF (abscisic acid [ABA] signaling) mutant plants. Therefore, these results indicated that the biotic sugar, XOS, can elicit stomatal closure via salicylic acid signaling‐mediated production of ROS and NO, in a manner independent of ABA signaling.